2020
DOI: 10.1111/epi.16527
|View full text |Cite
|
Sign up to set email alerts
|

Signal quality and patient experience with wearable devices for epilepsy management

Abstract: Noninvasive wearable devices have great potential to aid the management of epilepsy, but these devices must have robust signal quality, and patients must be willing to wear them for long periods of time. Automated machine learning classification of wearable biosensor signals requires quantitative measures of signal quality to automatically reject poor‐quality or corrupt data segments. In this study, commercially available wearable sensors were placed on patients with epilepsy undergoing in‐hospital or in‐home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 34 publications
1
87
0
1
Order By: Relevance
“…ORCID Sándor Beniczky https://orcid.org/0000-0002-6035-6581 Samuel Wiebe https://orcid.org/0000-0002-1061-9099 Numerous studies demonstrated that patients, caregivers and healthcare personnel need wearable seizure detection devices. [13][14][15][16][17][67][68][69]…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…ORCID Sándor Beniczky https://orcid.org/0000-0002-6035-6581 Samuel Wiebe https://orcid.org/0000-0002-1061-9099 Numerous studies demonstrated that patients, caregivers and healthcare personnel need wearable seizure detection devices. [13][14][15][16][17][67][68][69]…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…By remotely measuring ANS function, RMTs can equip patients with person-specific protocols that complement their daily routines and lifestyle, in addition to integrating their clinical and psychosocial profiles to passively and actively collect objective contextualized data in day-to-day life over numerous timepoints. RMT-based EGG, such as Bytflies ( ), has begun to be used in epilepsy ( 85 ) and provides well-powered and contextualized data that we are using to remotely examine low-frequency spectral power in DLB ( 86 ), as longer EEG recordings in real-world settings will provide more sensitive signatures of brain changes and are more likely to capture acute episodes of FC or VH than lab-based EEG. We are also using RMTs to passively collect remote data on cardiovascular (e.g., orthostatic hypotension, postprandial hypotension) and thermoregulatory (e.g., anhidrosis, compensatory hyperhidrosis) ANS function in potential DLB cases to unmask any dysautonomia indicative of alpha-synucleinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of a sensor has to be extensively studied before the implementation. Prior reports pointed to unique problems related to the biosensors, although this was not the uniform case [ 12 , 16 , 19 , 20 ]. Movement, skin color, and sweating were quite often reported as the main reasons for interference [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%